RELASI KONTEKTUALISASI AGAMA DAN BUDAYA LOKAL DALAM KEHIDUPAN MASYARAKAT INDONESIA - Septian Fiktor Riyantoro; Kurnia Ari Setiawan (JUSTITIA : Jurnal Ilmu Hukum dan Humaniora, 2022)
This study aims to discuss the emerging issues in Relations and Contextualization of Culture and Religion related to religion and customs affecting each other. Anthropology and Sociology approach with adat theory and 'Urf is used in this research. The argument emerges that Adat and 'Urf must be functional with people's lives. Therefore, the truth of Adat and 'Urf should be clarified before the concepts of Adat and 'Urf is understandable and appropriately implemented. Based on this statement, this study explains how the relationship between Religion and Culture is under the theory of 'Urf, To the concept stick to the original Law. The concept does not oppose the way of sharia law'. Besides that, the concept does not necessarily against extinct the existing customs in people's lives. The traditional culture that has been applied in the community as a community character in religion and culture is conserved by the 'Urf